Effect of Rambutan Leaf Extract (Nephelium lappaceum L.) on Colony Diameter and Percentage of Growth of Inhibition Fusarium oxysporum - Fauziahtul Azmi (Universitas Negeri Padang, 2021)
Abstract. Wilt disease is caused by the fungus Fusarium oxysporum. This fungus is difficult to eradicate and can survive in the soil for a long time. This disease causes considerable damage to plants. To control this disease, many farmers use synthetic fungicides. The continuous use of synthetic fungicides is not good for humans and the environment. To overcome this problem, plant-derived pesticides are used. Nephelium lappaceum L. (Rambutan) is a plant that has the potential as a vegetable pesticide.leaf extract N. lappaceum contains several antifungal compounds, namely saponins, tannins, and flavonoids. The purpose of this study was to examine the effect of leaf extract concentration of N. lappaceum on colony diameter and the percentage of inhibition of growth of F. oxysporum. This research was carried out from February 2021 to April 2021, at the Integrated Research Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This study was an experimental study consisting of 5 treatments and 3 replications with the administration of leaf extract at N. lappaceum concentrations of 0%, 10%, 20%, 30%, 40%. The data obtained were analyzed by means of variance (ANOVA) with Duncan's New Multiple Range Test (DNMRT) further test.. The results showed that the leaf extract of N. lappaceum. effect on the growth of fungal colonies of F. oxysporum. Each treatment was significantly different from the control and each treatment showed significant differences from each other. The concentration of leaf extract affected the percentage of growth inhibition of F.oxysporum. The lowest percentage of inhibition was at a concentration of 10% and the highest was at a concentration of 40%.Abstrak. Penyakit layu fusarium disebabkan oleh jamur Fusarium oxysporum. Jamur ini sulit dibasmi dan dapat bertahan di tanah untuk waktu yang lama. Penyakit ini menyebabkan kerusakan yang cukup besar pada tanaman. Untuk mengendalikan penyakit ini petani banyak menggunakan fungisida sintetik. Penggunaan fungisida sintetik secara terus menerus berdampak tidak baik bagi manusia dan lingkungan. Untuk mengatasi masalah tersebut maka digunakan pestisida nabati yang berasal dari tumbuhan. Nephelium lappaceum L. (Rambutan) merupakan salah satu tanaman yang berpotensi sebagai pestisida nabati. Ekstrak daun N. lappaceum mengandung beberapa senyawa yang bersifat antifungi yaitu saponin, tanin, dan flavonoid. Tujuan penelitian ini untuk melihat pengaruh konsentrasi ekstrak daun N. lappaceum terhadap diameter koloni dan persentase penghambatan pertumbuhan F. oxysporum. Penelitian ini dilaksanakan pada bulan Februari 2021 hingga April 2021, bertempat di Laboratorium Penelitian Terpadu Jurusan Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Padang. Penelitian ini merupakan penelitian eksperimen yang terdiri dari 5 perlakuan dan 3 ulangan dengan pemberian ekstrak daun N. lappaceum konsentrasi 0%, 10%, 20%, 30%, 40%. Data yang diperoleh dianalisis dengan sidik ragam (ANOVA) dengan uji lanjut Duncan’s New Multiple Range Test (DNMRT). Hasil penelitian menunjukkan bahwa ekstrak daun N. lappaceum. berpengaruh terhadap diameter koloni jamur F. oxysporum. Pada setiap perlakuan berbeda nyata dengan kontrol dan masing-masing perlakuan menunjukkan perbedaan yang nyata satu sama lain. Konsentrasi ekstrak daun berpengaruh terhadap persentase perhambatan pertumbuhan F.oxysporum. Persentase penghambatan terendah pada konsentrasi 10% dan paling tinggi pada konsentrasi 40%.